Respuesta :

[tex]\bf (\stackrel{x_1}{-10}~,~\stackrel{y_1}{-7})\qquad (\stackrel{x_2}{-5}~,~\stackrel{y_2}{-9}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{-9-(-7)}{-5-(-10)}\implies \cfrac{-9+7}{-5+10}\implies -\cfrac{2}{5}[/tex]


[tex]\bf \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-(-7)=-\cfrac{2}{5}[x-(-10)] \\\\\\ y+7=-\cfrac{2}{5}(x+10)\implies y+7=-\cfrac{2}{5}x-4\implies y=-\cfrac{2}{5}x-11[/tex]